HERTUG HANS OG HANS TROFASTE RIDDERE og deres eksklusive togter til rusuniverset - Elmeland, Karen (Tidsskriftet Antropologi, 1998)
Karen Elmeland: Hans the Duke, and His Loyal Knights: Their Exclusive Journeys to the World of Ecstasy This article describes an observational study performed during the project “Danish Alcohol Culture - Ecstasy, Ritual and 253 Regulation”. The aim of the study was to describe the alcohol culture of the “beer fratemity” gnaslguF. The focus was partly on the analysis of the cultural norms and the collective mechanisms of control influencing the use of alcohol and ecstasy among the members, partly on the analysis of the ritual structures goveming and forming the conviviality in different drinking situations. The overall aim of the project was to give a qualitative description of ecstasy as a State of consciousness - a non-everyday consciousness. In this article it is aigued that ritual analysis can be of relevance to understanding the ways in which Danes - and others for that matter - drink. Following this line of thinking, two ritual forms are identified: a rite of passage and a rite of fratemization. In both forms a four-stage structure can be identified.